2001
DOI: 10.1021/tx010012d
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Tamoxifen-DNA Adducts in the Liver of Rats and Mice

Abstract: A new HPLC gradient system was developed for (32)P-postlabeling analysis to identify and quantify hepatic tamoxifen-DNA adducts of rats and mice treated with tamoxifen. Four stereoisomers of alpha-(N(2)-deoxyguanosinyl)tamoxifen (dG(3')(P)-N(2)-TAM), alpha-(N(2)-deoxyguanosinyl)-N-desmethyltamoxifen (dG(3')(P)-N(2)-N-desmethyl-TAM), and alpha-(N(2)-deoxyguanosinyl)tamoxifen N-oxide (dG(3')(P)-N(2)-TAM N-oxide) were prepared by reacting either alpha-acetoxytamoxifen, alpha-acetoxy-N-desmethyltamoxifen or alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…These findings agree with previous studies indicating that DMBA and TAM can lead to DNA adduct formation. This injury is responsible for the activation of metabolic pathways that contribute for DNA fragmentation and the induction of cell death by apoptosis or necrosis, depending on the dose and the duration of exposure to the drug (Bursch et al, 1997;Umemoto et al, 2001;Barbisan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with previous studies indicating that DMBA and TAM can lead to DNA adduct formation. This injury is responsible for the activation of metabolic pathways that contribute for DNA fragmentation and the induction of cell death by apoptosis or necrosis, depending on the dose and the duration of exposure to the drug (Bursch et al, 1997;Umemoto et al, 2001;Barbisan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…formed through O-sulfonation of α-hydroxylated TAM metabolites (8); α-(N 2 -deoxyguanosinyl)tamoxifen (dG-N 2 -TAM) and α-(N 2 -deoxyguanosinyl)-Ndesmethyltamoxifen (dG-N 2 -N-desTAM) are detected as major hepatic DNA adducts using mass-spectroscopic and 32 P-postlabeling/HPLC analyses (12,15). There is a controversy regarding the detection of TAM-DNA adducts in the human tissues (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…When mice were treated with TAM (20 mg/ kg/day for 7 days) at the dose equivalent to that used for rat study, only a trace of TAM-DNA adduct (Ͻ1 adduct/10 8 nucleotides) was observed in the liver (data not shown). Therefore, mice were treated with a 6-fold higher dose (120 mg/kg/day) of TAM, as reported previously (Umemoto et al, 2001). A high level of TAM-DNA adducts was observed in the liver of all Xpc knockout mice (Fig.…”
Section: Repair Of Tamoxifen-dna Adducts In Rodentsmentioning
confidence: 56%
“…1) (Osborne et al, 1996;Dasaradhi and Shibutani, 1997). dG-N 2 -TAM and ␣-(N 2 -deoxyguanosinyl)-N-desmethyltamoxifen (dG-N 2 -N-desTAM) were major adducts in the liver of rats and mice treated with TAM (Rajaniemi et al, 1999;Umemoto et al, 2001) and in several tissues including reproductive organs of monkeys treated with TAM Shibutani et al, 2003). ␣-(N 2 -Deoxyguanosinyl)tamoxifen N-oxide (dG-N 2 -TAM N-oxide) was detected as a minor adduct in mouse liver.…”
mentioning
confidence: 99%